Single‐dose intravenous iron in Southeast Asian heart failure patients: A pilot randomized placebo‐controlled study (PRACTICE‐ASIA‐HF). (18th January 2018) - Yeo, Tee Joo; Yeo, Poh Shuan Daniel; Hadi, Farid Abdul; Cushway, Timothy; Lee, Kim Yee; Yin, Fang Fang; Ching, Anne; Li, Ruili; Loh, Seet Yoong; Lim, Shir Lynn; Wong, Raymond Ching‐Chiew; Tai, Bee Choo; et al.
Abstract: Aims: Iron deficiency is highly prevalent in Southeast Asians with heart failure (HF) and associated with worse outcomes. This trial aimed to assess the effect of intravenous iron in Southeast Asians hospitalized with decompensated HF. Methods and results: Fifty patients hospitalized for acute decompensated HF, regardless of ejection fraction, with iron deficiency (defined as serum ferritin <300 ng/mL if transferrin saturation is <20%) were randomized to receive either one dose of intravenous ferric carboxymaltose (FCM) 1000 mg or placebo (0.9% saline) following HF stabilization and before discharge in two Singapore tertiary centres. The primary endpoint was difference in 6‐min walk test (6MWT) distance over 12 weeks, while secondary endpoints were quality of life assessed using validated Kansas City Cardiomyopathy Questionnaire (KCCQ) and Visual Analogue Scale (VAS). Improvement in 6MWT distance at Week 12 was observed in both FCM and placebo groups (from 252 ± 123 to 334 ± 128 m and from 243 ± 67 to 301 ± 83 m, respectively). Unadjusted analysis showed 6MWT distance for FCM exceeded that for placebo, but adjustment for baseline covariates and time attenuated this effect {adjusted mean difference between groups: 0.88 m [95% confidence interval (CI) −30.2 to 32.0, P  = 0.956]}. KCCQ overall summary and VAS were similar in both groups [adjusted mean difference: KCCQ −1.48 (95% CI −8.27 to 5.31, P  = 0.670) and VAS 0.26 (95% CI −0.33 to 0.86, P  = 0.386)]. FCM was well tolerated with no serious treatment‐related adverse events. Conclusions: Intravenous FCM administered pre‐discharge in Southeast Asians hospitalized with decompensated HF is clinically feasible. Changes in 6MWT distance should be measured beyond Week 12 to account for background therapy effects.